Newly elected members of the Tufts Alumni Council, 1963 - Duette (Tufts Archival Research Center, 2005)
8x10, (l to r) Edward Shea, Professor Elizabeth A. Weiant, Antonio de Jesus Cardozo, Catharine Stevens, Dr. Emmanuel Dutsch, Deborah Phillips